Uricases: reflections on recent developments in the management of challenging gout patients - Naomi Schlesinger; Dan Kaufmann (Exploration of Musculoskeletal Diseases)
Oral urate-lowering therapy (ULT) is key to treating gout. However, many patients receiving oral ULT do not achieve the target serum urate (SU) levels, partly because some patients cannot tolerate or have contraindications to their use, mainly due to comorbidities. This may lead to uncontrolled gout. In species other than humans and some non-human primates, uricase (urate oxidase) converts urate to allantoin, which is more readily excreted by the kidney. Exogenous uricases, considered “enzyme replacement therapy”, are a therapeutic option for patients with refractory or uncontrolled gout. Current uricases on the market include pegloticase and rasburicase. Uricase treatment rapidly reduces hyperuricemia and tophaceous deposits and improves the quality of life. This review discusses currently approved uricases on the market and some in development; how best to minimize flares, anti-drug antibody (ADA) formation, infusion reactions, and loss of efficacy, and combination with immunomodulation in patients with gout requiring uricase therapy.